Camphor‐Enabled Transfer and Mechanical Testing of Centimeter‐Scale Ultrathin Films. Issue 28 (21st May 2018) - Wang, Bin; Luo, Da; Li, Zhancheng; Kwon, Youngwoo; Wang, Meihui; Goo, Min; Jin, Sunghwan; Huang, Ming; Shen, Yongtao; Shi, Haofei; Ding, Feng; Ruoff, Rodney S.
Abstract: Camphor is used to transfer centimeter‐scale ultrathin films onto custom‐designed substrates for mechanical (tensile) testing. Compared to traditional transfer methods using dissolving/peeling to remove the support‐layers, camphor is sublimed away in air at low temperature, thereby avoiding additional stress on the as‐transferred films. Large‐area ultrathin films can be transferred onto hollow substrates without damage by this method. Tensile measurements are made on centimeter‐scale 300 nm‐thick graphene oxide film specimens, much thinner than the ≈2 μm minimum thickness of macroscale graphene‐oxide films previously reported. Tensile tests were also done on two different types of large‐area samples of adlayer free CVD‐grown single‐layer graphene supported by a ≈100 nm thick polycarbonate film; graphene stiffens this sample significantly, thus the intrinsic mechanical response of the graphene can be extracted. This is the first tensile measurement of centimeter‐scale monolayer graphene films. The Young's modulus of polycrystalline graphene ranges from 637 to 793 GPa, while for near single‐crystal graphene, it ranges from 728 to 908 GPa (folds parallel to the tensile loading direction) and from 683 to 775 GPa (folds orthogonal to the tensile loading direction), demonstrating the mechanical performance of large‐area graphene in a size scale relevant to many applications. Abstract : A camphor coating allows the transfer centimeter‐scale ultrathin films onto hollow substrates for uniaxial tensile testing (the camphor is sublimed away prior to loading). The intrinsic mechanical response of large‐scale single‐layer graphene is extracted from the mechanics of graphene supported by a 100 nm‐thick polycarbonate film. The tensile mechanics of 300 nm‐thick graphene oxide film samples are also tested with this new method.